Imbauan Kepala Daerah Berkaitan Kondisi Pasca Pandemi Covid-19: Kajian Wacana Kritis Tuturan Kepala Daerah di Jawa Tengah - Arfika Dhea Syaharani; Johana Prastika Alfa; Rachel Fatma Maharani Putri; Geta Fadzilatul Rahmadhani; Budhi Setiawan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The spread of the Covid-19 virus and the emergence of various variants became a global pandemic in just a matter of minutes. The Indonesian government swiftly implemented several policies to prevent the spread of the virus. In the pandemic phase which requires social distancing for the community. The government does not stop urging the public to always obey health regulations and protocols. Moreover, the role of regional governments is very central in handling the Covid-19 pandemic, even though they limit direct contact with the community, thanks to advances in science and technology, central or regional leaders can use social media to convey texts or videos in the form of appeals to the public. After passing through the pandemic phase, the time has come to rebuild and overcome various problems that have arisen due to the impact of the pandemic. Conditions after the Covid-19 pandemic have become the focus of attention of regional governments, including Regional Heads in Central Java. This research uses a qualitative research approach. The aim of qualitative research consists of describing the research object, expressing the meaning behind the phenomenon, and explaining the phenomenon that occurs. The method used is descriptive and content analysis. Data is obtained critically through speech discourse contained in content on social media and produces inferences regarding the use of spoken language as a form of speech act. The results of this research show that in the speech video of the Central Java Regional Head, Ganjar Pranowo, there is macro structure (thematic) analysis, superstructure (schematic) analysis and micro structure analysis. Macro structure analyzes discourse that influences thoughts, actions and implied ideologies. Superstructure analysis understands the way speech discourse is structured and the appearance of its interactions. Meanwhile, microstructural analysis reveals that the language conveyed by Ganjar Pranowo aims to achieve certain communications.